Processing of Undis Bean (Cajanus Cajan L.) and Iron-Folic Acid Supplementation Increase Hemoglobin and Hematocrit Levels Post-Blood Donation - I Wayan Saisnu Supta; Susy Purnawati; I Wayan Putu Sutirta Yasa (Green Publisher Indonesia, 2025)
This study aims to demonstrate the efficacy of processed pigeon pea (Cajanus cajan L.) combined with iron-folic acid supplementation in increasing hemoglobin and hematocrit levels following blood donation. Processing of Undis Bean (Cajanus cajan L.) and Iron-Folic Acid Supplementation Increase Hemoglobin and Hematocrit Levels Post-Blood Donation. This experimental research employed a randomized pre-test/post-test control group design. Sixty-four blood donors aged 17–65 years who successfully donated at the Badung Regency Red Cross Mobile Unit in July 2024 were enrolled and divided into two groups: control group (K) receiving iron-folic acid supplementation (IFAS) only, and treatment group (P) receiving IFAS with 50 grams of processed pigeon pea daily. The intervention was administered for 7 days, after which hemoglobin and hematocrit levels were examined using the Photometric Point of Care Testing (POCT) method. Results demonstrated significant increases in both hemoglobin and hematocrit levels between pre-test and post-test in each group (p=0.000). Comparison between groups revealed significantly greater hemoglobin increases in group P (p=0.028) and hematocrit increases in group P (p=0.015). This study concludes that providing processed pigeon pea combined with IFAS for 7 days significantly increases hemoglobin and hematocrit levels after blood donation, offering a practical nutritional intervention to support post-donation recovery.